Challenging Bias against Women Academics in Religion - Hartung, Colleen (Women in Religion, 2021)
The second volume in the Women in Religion series, Challenging Bias against Women Academics in Religion presents biographies about women in academia who study, research, and teach about the world's religious and spiritual traditions. It addresses the question of why so many women academics, who are themselves producers of secondary sources, are absent as biographical subjects in secondary literature generally and on digital knowledge platforms specifically. Authors variously challenge the exclusionary assumptions that underlie systemic bias in the production of secondary and tertiary sources about women. This critical engagement disrupts sourcing and writing conventions that support and perpetuate bias and creates the opportunity for more expansive and inclusive biographical narratives about women.